Pengaruh LKPD Rukun Tetangga Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas 3 pada Pembelajaran Pendidikan Pancasila SDN 1 Jepun Kabupaten Tulungagung - Rinata, Sindi; Septiana, Ayu Rizki (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This research is motivated by the low critical thinking skills of students in Pancasila Education learning due to the teacher-centered learning process. This study aims to determine the effect of the use of Student Activity Sheets (LKPD) on Neighborhood Association (RT) material on the critical thinking skills of third-grade students of SDN 1 Jepun, Tulungagung Regency. The study used a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The sample consisted of 31 students in the experimental group and 35 students in the control group selected through purposive sampling. Both groups were given a pretest and posttest to measure changes in critical thinking skills after learning. The descriptive test instrument has been tested for validity using Exploratory Factor Analysis (KMO = 0.757; Bartlett's Test, p < 0.001) and reliability using Cronbach's Alpha (α = 0.808). Before testing the hypothesis, prerequisite tests were conducted in the form of normality and homogeneity tests. The data were then analyzed using the Independent Samples T-Test with the help of JAMOVI 2.6.44. The results showed that the posttest average for the experimental group was 86.8 and the control group was 76.1. The t-test produced t = 4.89 with p < 0.001, so that LKPD had a significant effect on students' critical thinking skills.